Variation of stress intensity factor and elastic T-stress along the crack-front in finite thickness plates - S. K. Kudari; K. G. Kodancha (Fracture and Structural Integrity)
Non-singular terms in the series expansion of the elastic crack-tip stress fields, commonly referred to as the T-stress. The T-stress is as an additional stress field characterizing parameter to stress intensity factor (K) in the analysis of cracked bodies. T-stress is used as an important constraint parameter in the fracture analysis. In this investigation, three-dimensional finite element analyses have been conducted to compute the elastic T-stress considering a single edge notched tensile (SENT) specimen with varied thickness and a/W ratio. The results indicate that the T-stress depends on the specimen thickness and significantly varies along the crackfront from surface to centre of the specimen. The T-stress results obtained in the present analysis together with corresponding KI values can be used for analysis of constraint effects in a fracture specimen.